Chewing Stimulation Reduces Appetite Ratings and Attentional Bias toward Visual Food Stimuli in Healthy-Weight Individuals - Ikeda, Akitsu; Miyamoto, Jun J.; Usui, Nobuo; Taira, Masato; Moriyama, Keiji (Frontiers in Psychology, 2018)
Based on the theory of incentive sensitization, the exposure to food stimuli sensitizes the brain’s reward circuits and enhances attentional bias toward food. Therefore, reducing attentional bias to food could possibly be beneficial in preventing impulsive eating. The importance of chewing has been increasingly implicated as one of the methods for reducing appetite, however, no studies to investigate the effect of chewing on attentional bias to food. In this study, we investigated whether chewing stimulation (i.e. chewing tasteless gum) reduces attentional bias to food as well as an actual feeding (i.e. ingesting a standardized meal) does. We measured reaction time, gaze direction and gaze duration to assess attentional bias toward food images in pairs of food and nonfood images that were presented in a visual probe task (Experiment 1, n = 21) and/or eye-tracking task (Experiment 2, n = 20). We also measured appetite ratings using visual analogue scale. In addition, we conducted a control study in which the same number of participants performed the identical tasks to Experiments 1 and 2, but the participants did not perform sham feeding with gum-chewing/actual feeding between tasks and they took a rest. Two-way ANOVA revealed that after actual feeding, subjective ratings of hunger, preoccupation with food, and desire to eat significantly decreased, whereas fullness significantly increased. Sham feeding showed the same trends, but to a lesser degree. Results of the visual probe task in Experiment 1 showed that both sham feeding and actual feeding reduced reaction time bias significantly. Eye-tracking data showed that both sham and actual feeding resulted in significant reduction in gaze direction bias, indexing initial attentional orientation. Gaze duration bias was unaffected. In both control experiments, one-way ANOVAs showed no significant differences between immediately before and after the resting state for any of the appetite ratings, reaction time bias, gaze direction bias, or gaze duration bias. In conclusion, chewing stimulation reduced subjective appetite and attentional bias to food, particularly initial attentional orientation to food. These findings suggest that chewing stimulation, even without taste, odor, or ingestion, may affect reward circuits and help prevent impulsive eating.